Globalization and Ttechnology Absorption in Europe and Central Asia : The Role of Trade, FDI, and Cross-Border Knowledge Flows - Goldberg, Itzhak (Washington, DC : World Bank, 2012)
This study analyzes the extent of knowledge and technology absorption for firms in Europe and Central Asia (ECA), as well as the factors that influence absorption, using statistical analyses of various data sources, including the World Bank enterprise surveys, patent databases maintained by the United States (U.S.) and European patent offices, and case studies. The study addresses the following issues: (i) what can we learn from patents and patent citations about international knowledge flows and cross-national technological cooperation in ECA? (ii) How does openness to trade, participation in global supply networks, and investment in human capital, via on-the-job training, enhance knowledge and technology absorption in ECA-region manufacturing firms? How does foreign direct investment (FDI) stimulate acquisition of managerial and technical skills, new machinery and equipment, and market development?